O impacto da qualidade das vias nas políticas de reabastecimento de transportadores rodoviários de carga - Silva, Henrique Lugon Ferreira (2015)
Due to its importance growth over the years within a company or in its supply chain, logistics decisions increasingly affect business in the categories of competitiveness and customer and shareholders added value. Within the scope of logistics, because it has a fundamental importance and a visible cost, transportation traditionally receives large managerial attention. Spending on fuels represent 35% of the total cost for road freight companies carriers. When analyzed the fuel costs, variations in prices were observed between regions, states and cities, which makes the total fuel cost of a vehicle, performing a route, depend directly on how the replenishment policy is set. Another condition that influences road transport costs is the conservation status of the pavement. Besides being essential for the country development, reducing accidents and sustainability, road infrastructure influence on travel times, vehicle operating costs and emissions. In this context, the study aims to propose the development of a mathematical model of decision-making, to establish a fuel refueling policy for a fixed route considering the variation in fuel prices along the route and the impact of pavement quality of Brazilian highways on these routes. As a result, we observe that the quality of Brazilian roads interferes in the refueling policy for a fixed route. It is hoped that this model can assist road carriers in decisionmaking and thereby significantly reducing their transportation costs.